2017
DOI: 10.1371/journal.pntd.0006045
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative label-free proteomic analysis of human urine to identify novel candidate protein biomarkers for schistosomiasis

Abstract: BackgroundSchistosomiasis is a chronic neglected tropical disease that is characterized by continued inflammatory challenges to the exposed population and it has been established as a possible risk factor in the aetiology of bladder cancer. Improved diagnosis of schistosomiasis and its associated pathology is possible through mass spectrometry to identify biomarkers among the infected population, which will influence early detection of the disease and its subtle morbidity.MethodologyA high-throughput proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Advanced proteomic analysis has led to high-throughput profiling of bladder cancer-related proteins with both high sensitivity and specificity, which has resulted in a wealth of informative biomarkers [16]. A similar strategy was utilized in a recent study that identified 54 potential protein biomarkers of bladder schistosomiasis by quantitatively comparing urinary samples from humans [17]. Other types of omics applications, such as genomics, epigenomics, transcriptomics and metabolomics, were also applied to determine biomarkers of bladder schistosomiasis.…”
Section: Multi-omics Application For Bladder Bio-marker Developmentmentioning
confidence: 99%
“…Advanced proteomic analysis has led to high-throughput profiling of bladder cancer-related proteins with both high sensitivity and specificity, which has resulted in a wealth of informative biomarkers [16]. A similar strategy was utilized in a recent study that identified 54 potential protein biomarkers of bladder schistosomiasis by quantitatively comparing urinary samples from humans [17]. Other types of omics applications, such as genomics, epigenomics, transcriptomics and metabolomics, were also applied to determine biomarkers of bladder schistosomiasis.…”
Section: Multi-omics Application For Bladder Bio-marker Developmentmentioning
confidence: 99%
“…This study was performed to establish homology of the 36 biomarker proteins evaluated in a previous study (Onile et al, 2017) in other schistosome species. It was found that protein homologues of the 36 S. mansoni biomarker proteins are present in S. haematobium and S.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…Phosphopyruvate hydratase, elongation factor 1-alpha and putative actin-1 protein have been identified as eggshell protein markers that can induce cellular or antibody responses and may be useful schistosomiasis diagnostic candidates. They have also been identified as putative S. mansoni biomarker proteins (Onile et al, 2017). They all have homologues in both S. haematobium and S. japonicum with many conserved regions and semi conserved regions in the multiple sequence alignment ( Figure 4.10).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
See 2 more Smart Citations